Kajian Eksperimen Pengaruh Rasio Diameter Silinder Di Depan Returning Blade Turbin Angin Savonius Myring N=1 Dengan Fin - Maulana Jalalluddin Safii; Priyo Agus Setiawan; Eky Novianarenti (Politeknik Perkapalan Negeri Surabaya, 2023)
Savonius wind turbine have the lowest efficientcy compared to other wind turbines. Based on the previous research, additional interfering cylinder and fin to the turbine was less efficient so there is still an opportunity to improved. Based on this condition, the experimental study was carried out by adding 1 fin to each turbine blade and placing an interfering cylinder in front returning blade to determine its improvement. It aslso compared between both of them in the experimental also used the myring equation n=1. Wind turbine dimension was 40 cm and variation of interfering cylinder diameter ratio was ds/d = 0,4;0,5;0,6; and 0,7. The speed variation was 5 m/s, 6 m/s and 7 m/s. The best performance of the savonius myring n=1 wind turbine is obtained at ds/d = 0,4 at a speed of 6 m/s. The coefficient of torque (Ct) performance increase 21.47% and the coefficient of power (Cp) 89.80%